Investigating the Consequences of the Socio-Instrumental Use of Enterprise Social Media on Employee Work Efficiency: A Work-Stress Environment - Wu, Shuhui; Pitafi, Abdul Hameed; Pitafi, Sheena; Ren, Minglun (Frontiers in Psychology, 2021)
Enterprise social media (ESM) has been widely adopted by firms for employee work-related communication. However, it is still debatable how such usage benefits work stress and employee work efficiency. Applying the transactional theory of stress, this study examined the impact of resilience as a moderator on the link between work stressors and individual work efficiency. A total of 285 entries were used to analyze the proposed hypothesis, using structural equation modeling (SEM) technique and hierarchical regression analysis on SPSS 21.0 and AMOS 21.0 software. According to the findings, ESM use has a considerable impact on work stresses (challenge and hindrance). The findings also revealed that challenge stressors have a beneficial influence on employee work efficiency, while hindrance stressors have a negative impact on it. Furthermore, the results also indicated that resilience strengthens the positive relationship between challenge-stressed employees and work efficiency. However, the findings also revealed that resilience reduces the negative association between hindrance-stress and work efficiency. Finally, the author also explored the study's implications for theory and management.